(untitled) (Faridpur Medical College Journal, 2012)
Bangladesh is densely populated country where male and female ratio is closer to each other. This descriptive study investigates the gender disparity of postmortem examination findings among 7 districts in the Rajshahi division of Bangladesh. Postmortem (PM) examination stations were located in Rajshahi, Rangpur, Bogra and Dinajpur Medical Colleges & Pabna, Natore and Chapai Nawabganj Sadar Hospitals. The findings of the autopsy reports (Total 3164) over the two years (2004 & 2005) were collected retrospectively from the register book of the authority. In this study we wanted to find out gender disparity - if exists in PM examination findings and, to what extent. Manually verified data were analyzed employing SPSS/WIN V-11.5. An obvious gender disparity existed in overall occurrence of unnatural deaths, male predominate female victims (M: F ratio = 1.51:1). A significant association existed in death circumstances & gender (p<0.0001); male (634) outnumbered female (250) in homicidal deaths, in suicidal deaths female (612) outnumbered male (364) and in accidental deaths male (583) outnumbered female (135). This classical gender difference in death circumstances remains similar to our national context. Findings of this study revealed an obvious gender difference in the overall numbers of cadaveric PM examination. Males were more victimized than females in majority of medico-legal aspects analyzed, except in suicidal cases. DOI: http://dx.doi.org/10.3329/fmcj.v7i1.10293 Faridpur Med. Coll. J. 2012;7(1): 23-25